Genetic Effects on Aggregation Behavior of Beetles - Bhagat, Mira; Marshall, Jeremy (My University, 2018)
Aggregations of insects can often cause problems because they consume large amounts of resources. Species like the Red Flour Beetle are particularly damaging because they can invade locations where humans store food (Lles 2018). Interestingly, different genetic strains of the Red Flour Beetle produce different amounts of aggregation pheromone (Gerken, Scully, Campbell 2018). Here, we tested if two different genetic strains of Red Flour Beetle formed aggregates based on their genetic background or their recent living environments. We found that beetles aggregated based on genetic factors, with environmental conditions being relatively weak. These data suggest that understanding the genetic background of pest insects can shed light on their behavior.
Keywords: Fall 2018